2006
DOI: 10.1111/j.1468-3083.2006.01718.x
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of dermoscopy for diagnosing pigmented Spitz nevus occurring on the glabrous skin

Abstract: References1 Sherer DW, Sapadin AN, Lebwohl MG. Pseudoxanthoma elasticum: an update. Dermatology 1999; 199: 3-7. 2 Viljoen DL, Beatty S, Beighton P. The obstetric and gynaecological implications of pseudoxanthoma elasticum. Br J Obstet Gynaecol 1987; 94: 884 -888. 3 Bercovitch L, Leroux T, Terry S, Weinstock MA. Pregnancy and obstetrical outcomes in pseudoxanthoma elasticum. Br

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Due to its rarity, dermoscopic findings of PSN on glabrous skin are not well known. To our knowledge, only one report described PSN on the palm, which showed a starburst pattern 2 . Here, we report a case of PSN on the sole with characteristic dermoscopic findings.…”
mentioning
confidence: 70%
“…Due to its rarity, dermoscopic findings of PSN on glabrous skin are not well known. To our knowledge, only one report described PSN on the palm, which showed a starburst pattern 2 . Here, we report a case of PSN on the sole with characteristic dermoscopic findings.…”
mentioning
confidence: 70%
“…Given the challenge of distinguishing benign from malignant lesions on clinical grounds, noninvasive imaging modalities to improve diagnostic accuracy and avoid unnecessary surgical procedures have been studied. Dermoscopy has been used to characterize acral Spitz nevi . One such case on the finger of a 3‐year‐old boy was found to demonstrate changes in dermoscopy over a 6‐month period .…”
Section: Discussionmentioning
confidence: 99%
“…This case suggested that different morphologic expressions over time on dermoscopy may correspond to varying evolutionary phases. In addition to the traditionally described dermoscopic patterns of starburst and globular arrangements, Nakagawa and colleagues described a novel pattern of crista transverse dots on dermoscopy in a palmar Spitz nevus on an adolescent boy …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested two typical dermoscopic patterns (globular and starburst) of Spitz nevus might be considered different morphologic expressions corresponding to the evolutionary phases of pigmented Spitz nevus. Another case was noted on the right palmar surface of a 9-year-old girl patient 10 . In that previous report, dermoscopy was demonstrated to be a valuable tool for making the diagnosis of pigmented Spitz nevus, even on the glabrous skin.…”
Section: Discussionmentioning
confidence: 99%